Driver's Seat: Understanding Divergent Zoochorous Dispersal of Propagules - Coughlan, Neil E.; Dickey, James W. E.; Cuthbert, Ross N.; Kelly, Thomas C.; Jansen, Marcel A. K.; Dick, Jaimie T. A. (Frontiers in Ecology and Evolution, 2019)
The mechanisms which underpin passive dispersal (zoochory) of organisms (or propagules) by other, usually more mobile animals (vector species), are frequently poorly understood. While certain dispersal networks have received considerable scientific interest, basic questions concerning the relative importance of vector species, propagule survival, and likely dispersal distances, often remain unanswered. Here, we propose and apply a series of novel metrics, the Dispersal Potential (DP), the Relative Dispersal Potential (RDP) and the Combined Dispersal Potential (CDP), to predict and classify likely dispersal and vector importance. In essence, DP = Np × Tv, whereby Np is the per capita propagule load (e.g. mean, minimum, or maximum abundance) or species richness of propagules carried per individual vector species, while Tv is the total number of possible vectors (e.g. individuals of a single species at a source site, local scale abundances, or entire continental populations). Further, the ratio based metric RDP allows for DP comparison between species, while the CDP accumulates the DP of a variety of vector species. An additional Relative CDP (RCDP) metric facilitates comparison between the CDP for multiple vectors to that of one or more additional vectors. The proposed metrics can also be used to assess intraspecific differences (e.g. ontogeny or reproductive status). Accordingly, we examine a variety of case studies and present calculations to ascertain the usefulness of our proposed metrics. Finally, we argue that adoption of these metrics and variants thereof, will enhance understanding of zoochory within and across dispersal networks.